2011
DOI: 10.1073/pnas.1106427108
|View full text |Cite
|
Sign up to set email alerts
|

Thaumarchaeotes abundant in refinery nitrifying sludges express amoA but are not obligate autotrophic ammonia oxidizers

Abstract: Nitrification is a core process in the global nitrogen cycle that is essential for the functioning of many ecosystems. The discovery of autotrophic ammonia-oxidizing archaea (AOA) within the phylum Thaumarchaeota has changed our perception of the microbiology of nitrification, in particular since their numerical dominance over ammonia-oxidizing bacteria (AOB) in many environments has been revealed. These and other data have led to a widely held assumption that all amoA-encoding members of the Thaumarchaeota (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
234
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 69 publications
19
234
1
4
Order By: Relevance
“…In some cases it has been reported that the archaeal amoA gene could be an evolutionary relict that is not functional anymore (Mussmann et al, 2011). Nonetheless, in Lake Redon the match found between the vertical abundance of nitrite and peaks in the abundance of both amoA and 16 S rRNA genes strongly suggests potential active ammonium oxidation zones related to archaea.…”
Section: Discussionmentioning
confidence: 90%
“…In some cases it has been reported that the archaeal amoA gene could be an evolutionary relict that is not functional anymore (Mussmann et al, 2011). Nonetheless, in Lake Redon the match found between the vertical abundance of nitrite and peaks in the abundance of both amoA and 16 S rRNA genes strongly suggests potential active ammonium oxidation zones related to archaea.…”
Section: Discussionmentioning
confidence: 90%
“…All six carbon fixation pathways known to date (Berg et al, 2010) were incomplete or undetectable in Fn1 (Supplementary Figure S5a). This latter feature is distinct from other sequenced thaumarchaeal and autotrophic crenarchaeal genomes (Berg et al, 2010;Beam et al, 2014;Konneke et al, 2014), further building on previous evidence which suggests a more versatile metabolism for members of the Phylum Thaumarchaeota (for example, bacterial ectosymbionts (Muller et al, 2010) and facultative ammonia oxidizers (Mussmann et al, 2011)). Fn1 is not predicted to ferment pyruvate to end products such as acetate, butyrate, ethanol, H 2 , lactate, and propionate (Supplementary Table S3).…”
mentioning
confidence: 91%
“…Despite their abundance and biogeochemical importance, fundamental questions remain regarding the physiology and metabolism of MGI. Several studies of MGI have provided evidence for both autotrophic ammonia oxidation (Konneke et al, 2005;Ingalls et al, 2006) and heterotrophy (Ouverney and Fuhrman, 2000;Agogué et al, 2008;Mubmann et al, 2011;Tourna et al, 2011). Autotrophic ammonia oxidation has now been confirmed in a few cultured representatives (De La Torre et al, 2008;Tourna et al, 2011), including Nitrosopumilus maritimus (Konneke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies of cultures and surface waters indicate autotrophy, observations of a lower ratio of MGI amoA to 16S rRNA gene copies (Agogué et al, 2008) and decreasing MGI carbon fixation with depth (Varela et al, 2011) in the Atlantic suggest that deep-sea MGI are predominantly organoheterotrophic. Recent studies also show that the presence (and expression) of amoA genes does not necessarily indicate CO 2 fixation (Mubmann et al, 2011;Tourna et al, 2011). The GB metagenome contains genes homologous to N. maritimus genes encoding the 3-hydroxypropionate/ 4-hydroxybutyrate pathway for CO 2 fixation (Berg et al, 2007), including 4-hydroxybutyryl-CoA dehydratase, methylmalonyl-CoA epimerase and mutase, and acetyl-CoA carboxylase.…”
Section: Species-resolved Transcriptomics Of Ammonia Oxidation Genesmentioning
confidence: 99%
See 1 more Smart Citation